The Role of Customs in Internasional Trade and National Economic Protection - Susena, Karona Cahya; Hidayah, Nenden Restu; Tambuan, Oscar Julius Gamaliel (Utami Publisher, 2025)
This article discusses the influence of tax rates and understanding of taxation on the level of taxpayer compliance in Indonesia. Tax compliance is one of the main factors in the success of a country's taxation system. This article discusses the relationship between tax rates set by the government and taxpayer compliance, as well as how taxpayers' understanding of taxation can influence their behavior in fulfilling their tax obligations. Based on literature studies and several case examples, it was found that higher tax rates tend to reduce the level of taxpayer compliance, while a better understanding of tax obligations increases awareness and compliance. Apart from that, this article also discusses several external factors that can influence the level of compliance, such as government transparency and the effectiveness of tax supervision.